The return of the Duke—locality data for Megadytes ducalis Sharp, 1882, the world’s largest diving beetle, with notes on related species (Coleoptera: Dytiscidae) - Hendrich, Lars; Manuel, Michael; Balke, Michael (Zootaxa, 2019)
Megadytes (Bifurcitus) ducalis Sharp, 1882 is the largest diving beetle in the world and has been considered a candidate for the world’s rarest insect (Jones 2010). It was described from "Brazil", is only known from the male holotype in the Natural History Museum (London), and typically thought to be extinct. Here we report the finding of 10 additional specimens, all collected at the end of the 19th century, which were discovered incidentally in different historical collections, including drawers with unsorted diving beetle accessions of the Muséum National d’Histoire Naturelle (Paris). These specimens, whilst old, reveal exact locality data for the first time, enabling focused field campaigns to attempt to rediscover this giant alive. Locality labels all indicate Santo Antônio da Barra (present name Condeúba), in the southern part of Bahia, Brazil, suggesting that the species may have a restricted distribution in wetter parts of the Brazilian savanna or cerrado. We also describe the female of M. ducalis for the first time and present new records of the putatively closely related species Megadytes magnus Trémouilles & Bachmann, 1980 and M. lherminieri (Guérin-Méneville, 1829), the latter being recorded for the first time from Ecuador. These three morphologically similar species together form the subgenus Bifurcitus Brinck, 1945 and we provide photographs of their habitus, median lobes and other morphological details.